Multibeam bathymetry processed data (Wärtsilä ELAC 3050 MK II entire dataset) of RV POSEIDON during cruise POS526, North Sea - Iason-Zois Gazis; Mariliza Thomadaki; Jens Greinert (PANGAEA, 2023)
The DeepSea Monitoring group (https://www.geomar.de/deepsea-monitoring) acquired high-resolution ship-based multibeam echosounder (MBES) data in the Tisler Reef region (North Sea) during the POS526 expedition SeASOM: Semi-Autonomous Subsurface Optical Monitoring for methane seepage and cold-water coral studies in the North Sea. The ELAC (Wärtsila) Seabeam 3050 was used at 50kHz. The raw data were recorded in .XSE format. The post-processing was done using the QPS Qimera software v1.7 and included: Bias correction (roll, pitch, yaw), sound velocity correction, and 3D filtering of erroneous soundings. The final data was projected in the Universal Transverse Mercator (UTM) zone 31N and exported as a georeferenced grid (GeoTIFF) with a 5 m x 5 m cell size.